The oncogenic role of ecotropic viral integration site 1 in hematological malignancies: mechanisms of activation and leukemogenesis - Hao, Yuchao; Liu, Jing; Lou, Jiacheng; Yan, Jinsong (Frontiers in Immunology, 2026)
Ecotropic viral integration site 1 (EVI1), encoded by the EVI1 gene on chromosome 3q26.2, is a dual-domain zinc finger transcription factor that functions as a potent proto-oncogene in a wide spectrum of hematological malignancies. Under normal physiological conditions, its expression is tightly regulated and restricted primarily to hematopoietic stem cells and specific embryonic tissues. However, aberrant overexpression of EVI1 is a hallmark of aggressive myeloid leukemias, including acute myeloid leukemia (AML), myelodysplastic syndromes (MDS), and the blast crisis of chronic myeloid leukemia (CML). The oncogenic activation of EVI1 occurs through diverse genetic mechanisms, most notably chromosomal rearrangements involving the 3q26 locus, such as inv(3)(q21q26.2) and t(3;3)(q21;q26.2), which juxtapose the EVI1 gene with potent enhancers like that of GATA2. Other mechanisms include the formation of oncogenic fusion genes (e.g., AML1-EVI1, ETV6-EVI1), enhancer hijacking, and retroviral insertional mutagenesis. Once overexpressed, EVI1 drives leukemogenesis through multifaceted molecular actions. It acts as a master transcriptional regulator, profoundly disrupting normal hematopoietic differentiation by repressing key lineage-specific transcription factors like RUNX1 and interfering with cytokine-induced maturation. Concurrently, EVI1 promotes cell survival and proliferation by modulating critical signaling pathways, including the potent inhibition of the tumor-suppressive TGF-β pathway and the activation of the pro-survival PI3K/AKT/mTOR cascade via PTEN suppression. EVI1 also cooperates with a multitude of other oncogenic lesions, such as MLL rearrangements, AML1 mutations, and activated RAS signaling, to accelerate disease progression. Clinically, EVI1 overexpression is one of the most robust independent indicators of poor prognosis, associated with therapy resistance and reduced overall survival. This review provides a detailed discussion of the mechanisms underlying EVI1’s activation, its complex molecular functions in hematopoietic transformation, and its profound clinical implications in hematological malignancies.